Beyond Fundamentalism: A Path to Reframing Faith in Adolescents – Insights from Vocati - Smith, Jeremy D. (Journal of youth and theology, 2025)
A rise in mental health issues among youth, including increased stress, has been observed worldwide. The developmental stage of adolescence, characterised by physical, psychological, and social development, is one which can inherently be "stressful." Religion and spirituality can buffer stress. However, evidence suggests fundamentalist faith traditions may inadvertently contribute to unhealthy religious coping mechanisms, including increased stress. In this study, we conducted focus groups with youth and college mentors from fundamentalist backgrounds from 2016 to 2021 as a part of Vocati, a theology program for high school students. Participants were asked what they believed to be the "most important/significant issues associated with being Christian in a global world." Researchers recorded narrative comments using a descriptive-interpretive qualitative approach and analysed the data using interpretative phenomenological analysis. Qualitative themes emerging from the narrative data were "persecution," "hypocrisy," "conforming to culture," "divisiveness," and "judgemental" Christians. This paper explores the perceptions reported and offers practical suggestions for reconstructing faith formation in youth coming from fundamentalist backgrounds.